Sir Mohammad Shafi’s Contribution in Pakistan Movement - Syed Akmal Hussain Shah (JSSH, 2023)
Sir Syed School of thought played important role in promoting Indian Muslims’ cause and securing their interest on All India level. The group, following Sir Syed Ahmad Khan’s style of politics, presented Muslim demands before Lord Minto for the then upcoming reforms. Later on most of the demands were accommodated in the Act of 1909.